STRATEGI PEMASARAN PRODUK AIR MINUM DALAM KEMASAN “CI LEGON” OLEH PERUMDA AIR MINUM CILEGON MANDIRI DI WILAYAH KOTA CILEGON - Reina Yuniarsih; Candra Sigalingging (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Bottled drinking water (AMDK) has now become a consumptive product for society. Various factors are the reasons why people choose to consume bottled drinking water, so that the need for bottled drinking water is currently continuing to increase and this is a potential business opportunity that is being looked at by Perumda Air Minum Cilegon Mandiri which has recently launched a bottled drinking water product with brand